Sistem Informasi Layanan Hukum Gratis Studi Kasus: Kabupaten Musi Banyuasin - R.M. Nasrul Halim; Nurul Huda; Indra Juliansyah (Teknomatika, 2020)
Musi Banyuasin is one of the largest districts in South Sumatra. With the Vision and Mission "Muba Goes Forward 2022", The Government of Musi Banyuasin districts has launched various activity programs to achieve the vision and mission. One of them is the Free Legal Aid Program for the Poor people which is intended to provide legal aid to poor people in Musi Banyuasin districts. The obstacle faced by the Free Legal Aid Program is the difficulty of the community to register and the lack of socialization because it is only done through the distribution of circular letters. With a very large district area of course this Free Legal Aid Program can only be enjoyed by a few rural/subdistrict around the district Capital, and unreachable even known by the people of Musi Banyuasin district which are far away in remote villages/district. Therefore, a Free Legal Aid for peoples in Musi Banyuasin district web-based information system is needed, which is created using the waterfall software development method as a media for sharing information, socialization and registration which will facilitate the people to take part in this Free Legal Aid Program. With this web-based information system people can directly register the problem/legal case and immediately being followed up by the appointed Legal Aid Organization.